Click. Connect. Commit: How Social Media Marketing Builds Brand Loyalty on Indonesia's Leading E-Commerce Platforms - Ripaldi Krisnanta Hidayat; Kurniawati (Universitas Negeri Semarang, 2025)
This study investigates the indirect effect of social media marketing (SMM) on brand loyalty through the mediating roles of consumer brand engagement, brand trust, brand experience, and brand equity within Indonesia’s e-commerce industry. Although SMM plays a crucial role in shaping brand loyalty, few studies have comprehensively examined the relational and experiential variables underlying this process. A cross-sectional survey was conducted involving 285 active social media users who had previously made purchases via TikTok Shop, Shopee, or Tokopedia. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that SMM positively affects consumer brand engagement, brand trust, brand experience, and brand equity. However, SMM has a negative direct effect on brand loyalty. Conversely, all four mediating variables significantly and positively influence brand loyalty, suggesting that emotional interaction and meaningful brand experiences play a greater role than mere digital exposure in fostering loyalty. This study provides a holistic model for understanding digital relationship strategies. Practically, e-commerce companies are encouraged to shift their focus from purely promotional tactics to interactive content, personalized experiences, and trust-based communication to cultivate long-term consumer loyalty in an increasingly competitive digital environment.